2002
DOI: 10.1080/0036554021000026955
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acquiring Tick Bites in South-eastern Sweden

Abstract: The incidence and the temporal pattern of tick bites were studied in a population frequently out-of-doors in a tick-endemic area in south-eastern Sweden between May 2000 and March 2001. The participants, who were well aware of tick-borne diseases, inspected their skin daily from May until September and completed a diary sheet, registering visited geographical places, time out-of-doors, observed tick bites, etc. The participants were also given questionnaires in both the initial and final stages of the study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 17 publications
5
20
0
Order By: Relevance
“…The drop in requests in 1999, 2000 and 2001, is likely to be a consequence of the increased access to the internet. The seasonal pattern of requests was similar to the human tick bite distribution indicated by Stjernberg and Berglund (2002) in South-eastern Sweden, which supports the idea that the requests are originating from tick bites. The symptoms of Lyme borreliosis, e.g.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The drop in requests in 1999, 2000 and 2001, is likely to be a consequence of the increased access to the internet. The seasonal pattern of requests was similar to the human tick bite distribution indicated by Stjernberg and Berglund (2002) in South-eastern Sweden, which supports the idea that the requests are originating from tick bites. The symptoms of Lyme borreliosis, e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Small experimental studies have been performed on the interaction between humans and ticks (e.g., Jensen 2000a; Stjernberg and Berglund 2000;Stjernberg and Berglund 2002), but to our knowledge no long term studies have been published and presumably such observations do not exist. The type of study therefore has a 'missing link' status in the knowledge of tick borne diseases.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The prospective study in the LBendemic area in Sweden established a 0.5% risk of clinical infection with B. burgdorferi s.l. following a tick bite, in spite of a considerable infection of ticks in the area (15-26%) [31], and in a study in the USA the frequency of LB after a recognized tick bite was about 1% [32]. Thus, the risk of symptomatic or asymptomatic infection with B. burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 97%
“…men rather than women may contract more tick bites. However, a study on the risk for people to be infested by ticks in southernmost Sweden found no significant difference between men and women (Stjernberg & Berglund, 2002). A similar study on the western coast of Norway showed that women >50 years actually contracted more tick bites than similarly aged men and younger women (Hjetland et al, 2013).…”
Section: Are There Gender-and Geographical Differences In the Borrelimentioning
confidence: 94%